Absence of QTc prolongation with domperidone: A randomized, double‐blind, placebo‐ and positive‐controlled thorough QT/QTc study in healthy volunteers. Issue 1 (30th May 2014) - Biewenga, Jeike; Keung, Chi; Solanki, Bhavna; Natarajan, Jaya; Leitz, Gerhard; Deleu, Sofie; Soons, Paul
Abstract Domperidone effects on QTc duration were assessed in a single‐center, double‐blind, four‐way crossover study of 44 healthy participants randomized to one of four treatment sequences consisting of four treatment periods separated by 4–9 days washout. On Day 1 of each 4‐day period, participants began oral domperidone 10 or 20 mg q.i.d., matching placebo q.i.d., or single‐dose moxifloxacin 400 mg (positive control)/placebo q.i.d. In each period, triplicate 12‐lead electrocardiograms were recorded at baseline (30, 20, and 10 minutes predose), 8 timepoints after dosing on Days 1 and 4, and predose on Day 4. In mixed effects models, the largest difference for domperidone in least squares means for change from baseline QTcP versus placebo was 3.4 milliseconds (20 mg q.i.d., Day 4), 90% CI: 1.0–5.9, and <10 milliseconds at all timepoints for both domperidone dosages. Moxifloxacin response confirmed assay sensitivity. Participants achieved expected domperidone plasma exposures. No significant exposure‐response relationship was found for QTc increase per ng/mL domperidone (90% CI of the slope estimate included zero at mean Cmax on Day 1 or Day 4). In summary, domperidone at doses up to 80 mg/day did not cause clinically relevant QTc interval prolongation.